2019
DOI: 10.1177/1359105319871639
|View full text |Cite
|
Sign up to set email alerts
|

Self-concept, illness acceptance and depressive and anxiety symptoms in people with multiple sclerosis

Abstract: Little research has examined the relationship between self-concept and depressive and anxiety symptoms and whether this is moderated by illness acceptance in individuals with multiple sclerosis. Results of an online self-report survey completed by 515 individuals with multiple sclerosis revealed that self-concept was negatively associated with depressive and anxiety symptoms with illness acceptance moderating the association such that individuals with highest self-concept and illness acceptance had the lowest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 27 publications
0
5
1
Order By: Relevance
“…Despite existing evidence linking acceptance with anxiety in PwMS (Kiropoulos et al, 2021; Van Damme et al, 2016), acceptance of MS and optimism were the only nondemographic factors which did not significantly predict the variance in anxiety scores. However, examination of the findings shows how a number of modifiable factors are associated with anxiety.…”
Section: Discussioncontrasting
confidence: 65%
“…Despite existing evidence linking acceptance with anxiety in PwMS (Kiropoulos et al, 2021; Van Damme et al, 2016), acceptance of MS and optimism were the only nondemographic factors which did not significantly predict the variance in anxiety scores. However, examination of the findings shows how a number of modifiable factors are associated with anxiety.…”
Section: Discussioncontrasting
confidence: 65%
“…Acceptance is defined in terms of the lived experience of people with chronic illnesses, such as acceptance of the change, the definition of the self and behavioural adaptation (Stuifbergen et al, 2008). It was shown that acceptance was a predictor of good adjustment for patients with MS (Kiropoulos et al, 2019). Concerning the psychological outcomes of acceptance, Bogart (2015) reported that the development of disability identity, that is, acceptance of the disability into the self, was related to lower depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have investigated the impact of MS on patients' lives, referred to as biographical disruption. For example, Individuals with MS tend to have lower overall self-concept and physical selfconcept compared to healthy individuals (19,20). They may have negative attitudes towards their social relationships, moods, intelligence, and talent (21).…”
Section: Introductionmentioning
confidence: 99%